La semiotricidad como estrategia pedagógica para el fortalecimiento de las relaciones interpersonales en tres colegios distritales de la ciudad de Bogotá - Pacheco Villegas, Carlos Eduardo; Albarracín Reyes, José Gerardo; Rodríguez Valero, Francisco Javier (Educación y Ciudad, 2020)
Next, as a teaching experience, a pedagogical proposal is shared that strengthens interpersonal relationships through semiotricity as a constitutive element of what it can mean to educate man physically, since the contemporary school faces challenges of a social, cultural and human order that demand its visibility, and at the same time it challenges it to promote dynamics that correspond to the needs not only economic and of competitiveness, but ontological and social, where the encounter with the other allows the reunion with itself.